Development of plyometric exercises in learning physical education - Zuhar Ricky; Gingga Prananda; Erit Triana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
The problem’s background in this study’s the lack of variations in explosive power training used for leg muscles and the lack use of plyometrics in Physical Education courses. This resulted in the lower results of student's vertical jump jumps seen from the initial test of Physical, Health, and Recreation Education student's vertical jump. To overcome this, a plyometrics training model was developed to provide a Physical Education variety courses for the explosive power of student leg muscles. This research aims to develop a valid, practical, and effective plyometrics training model. This research type’s research and development with a 4D model (Define, Design, Develop, Dessiminate). The subjects of the plyometrics exercise trial were 6 Health and Recreation Physical Education students in 2020. The data collection instruments used were validation sheets, practicality sheets, effectiveness sheets, and vertical jump tests for explosive power. Analysis results on the validity test obtained an average value of 92.5% with a very valid category. Practicality test obtained an average of 76.52% with the practical category. Then in the effectiveness test, the average vertical jump jump test was obtained with an average of 67% with the effective category. Thus, it can be concluded that the plyometrics training model for Physical, Health, and Recreation Education students can be applied to their lectures ‘bout valid, practical and effective categories. Practicality test obtained an average of 76.52% with the practical category. Then in the effectiveness test, the average vertical jump jump test was obtained with an average of 67% with the effective category. Thus, it can be concluded that the plyometrics training model for Penjaskesrek students can be applied to Physical, Health, and Recreation Education’s lectures in valid, practical and effective categories. Practicality test obtained an average of 76.52% with the practical category. Then in effectiveness test, the average vertical jump test was obtained with an average of 67% with the effective category. Thus, it can be concluded that the plyometrics training model for Physical, Health, and Recreation Education students can be applied to their lectures in the valid, practical and effective categories.